Chronic Effects of Different Intensities of Power Training on Neuromuscular Parameters in Older People: A Systematic Review with Meta-analysis - Marcelo Bandeira-Guimarães; Eduarda Blanco-Rambo; Alexandra Ferreira Vieira; Mikel L. Sáez de Asteasu; Ronei S. Pinto; Mikel Izquierdo; Eduardo Lusa Cadore (SpringerOpen, 2023)
Abstract Background Power training (PT) has been shown to be an effective method for improving muscle function, including maximal strength, measured by one-repetition maximum (1RM), and power output in older adults. However, it is not clear how PT intensity, expressed as a percentage of 1RM, affects the magnitude of these changes. The aim of this systematic review (International prospective register of systematic reviews-PROSPERO-registration: CRD42022369874) was to summarize the evidence from randomized clinical trials (RCT) assessing the effects of low-intensity (≤ 49% of 1RM) and moderate-intensity (50-69% of 1RM) versus high-intensity (≥ 70% of 1RM) PT on maximal power output and maximal strength in older adults. Methods We included RCTs that examined the effects of different intensities of power training on maximum strength and power output in older people. The search was performed using PubMed, LILACS, Embase, and Scopus. Methodological quality was assessed using the preferred reporting items for systematic reviews and meta-analyses (PRISMA 2020 statement checklist), and the quality of evidence was determined using the PEDro scale. Data were analyzed using standardized mean differences (SMD) with a 95% confidence interval (CI), and random effects models were used for calculations. A significance level of p ≤ 0.05 was accepted. Results Three RCTs assessing 179 participants, all of high methodological quality, were included. There were no significant differences between different PT intensities in terms of power output gains for leg press [SMD = 0.130 (95% CI − 0.19, 0.45), p = 0.425] and knee extension exercises [SMD: 0.016 (95% CI − 0.362, 0.395), p = 0.932], as well as leg press 1RM increases [SMD: 0.296 (95% CI − 0.03, 0.62); p = 0.072]. However, high-intensity PT (70-80% of 1RM) was significantly more effective than low-intensity PT in increasing 1RM for knee extension exercise [SMD: 0.523 (95% CI 0.14, 1.91), p = 0.008]. Conclusions PT performed at low-to-moderate intensities induces similar power gains compared to high-intensity PT (70-80% of 1RM) in older adults. Nonetheless, the influence of PT intensity on lower-limb strength gains seems to be dependent on the assessed exercise. Cautious interpretation is warranted considering the inclusion of only three studies.